Indonesian Salt Import Policy as A Threat and Opportunity in The Concept of Blue Economy in Indonesia - Tomi Aris; Desi Albert Mamahit; Abdul Rivai Ras (LPPM Universitas Trunojoyo Madura, 2022)
Salt is a strategic resource or commodity with great potential and has not been appropriately managed. Indonesia, with a potential coastline of 81,000, has great potential to become a salt-exporting country, but currently, to meet the national salt demand, Indonesia must import salt. The right solution is needed to eliminate the problem of importing salt that occurs. The concept of the Blue Economy, which prioritizes economic growth from the marine and fisheries sector while ensuring the sustainability of resources and the coastal and marine environment, is closely related to the current salt import policy. This study aims to analyze the policy of importing salt from other countries to Indonesia as a threat or opportunity to realizing a Blue Economy in Indonesia. The method used in this study is a qualitative approach and the analysis used is PESTEL. It is recorded that 20 factors represent opportunities to import salt and 15 factors that threaten salt import. Even so, the study results show that the score for import opportunities is lower than the threat. From the score obtained, it can be concluded that although many factors encourage Indonesia to import salt, the urgency for Indonesia to import salt is still not too strong. This policy-making must be in line with the Blue Economy concept, which emphasizes the benefits and impacts of achieving welfare for the community. There needs to be a government policy to increase national salt production to suppress the increasing number of salt imports. The critical factor for its success is increasing the amount of domestic salt production. In the future, the results of this study can be used as material for consideration by the Indonesian government in developing national salt production